Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan terhadap Kebijakan Dividen pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2017 - Melsi Damayanti; Rita Nengsih; Zainuddin Zainuddin (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2018)
This study aims to examine the effect of profitability, liquidity and company size on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2017. this research was conducted on the Indonesia Stock Exchange. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange during the period of 2012 to 2017. The sampling technique was carried out by purposive sampling method. The criteria for the company to be sampled are manufacturing companies that are consistently listed on the Indonesia Stock Exchange in the period 2012-2017, routinely publish their financial reports and consecutively distribute dividends during the period of 2012 to 2017. Based on the above criteria, only 3 companies meet the criteria for sampling. The results of the research and hypothesis testing showed that the return on assets, current ratio and firm size together and partially affect dividend payout ratio in manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2017. The value of the correlation coefficient (R) of 0.614 shows that the correlation between the dependent variable (DPR) and the independent variables (ROA, CR and firm size) is 61.4%. The coefficient of determination (R2) of 0.377 means the ability of the independent variable in explaining the dependent variable is 37.7% and the remaining 62.3% is explained by other variables not included in this study.